A New Positive Definite Expanded Mixed Finite Element Method for Parabolic Integrodifferential Equations - Yang Liu; Hong Li; Jinfeng Wang; Wei Gao (Journal of Applied Mathematics)
A new positive definite expanded mixed finite element method is proposed for parabolic partial integrodifferential equations. Compared to expanded mixed scheme, the new expanded mixed element system is symmetric positive definite and both the gradient equation and the flux equation are separated from its scalar unknown equation. The existence and uniqueness for semidiscrete scheme are proved and error estimates are derived for both semidiscrete and fully discrete schemes. Finally, some numerical results are provided to confirm our theoretical analysis.